Determinants of Student’s Satisfaction Towards Bus Service Quality in UiTM Cawangan Selangor - Mat Hasan, Nor Zaihan; Anuar, Annurizal; Md Mansor, Mohamad Naqiuddin; Mohamad Besir, Mohamad Shahril (Information Management and Business Review, 2024)
Bus service around the campus is essential for the movement of students to undergo academic and co-curricular activities. Student satisfaction with the quality of the bus service provided needs to be considered. Hence, this study was conducted to determine the relationship between empathy, perceived value, reliability and timeliness and also to examine the greatest predictors among all four variables towards student satisfaction with the quality of bus services at UiTM Cawangan Selangor. In total, 200 undergraduate university students took part in the research as survey respondents. The SPSS version 29 was used to analyze the data. The findings from the analysis revealed that empathy, perceived value, reliability and timeliness were found significantly correlated with student satisfaction. In addition, the reliability was highly significant in determining student satisfaction. The practical and theoretical implications of understanding the characteristics of empathy, perceived value, reliability and timeliness will make university administrators and service providers more concerned with student satisfaction to improve the quality of bus services provided. In addition, the results of this study also aim to provide insights that can be taken into action by the parties concerned in improving service delivery and the overall student experience.